1984
DOI: 10.1073/pnas.81.19.5966
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4 mobilizes calcium without the breakdown of polyphosphoinositides and the production of phosphatidic acid in rabbit neutrophils.

Abstract: The addition of fMet-Leu-Phe, leukotriene B4, or arachidonic acid to rabbit neutrophils causes a rise in the level of intracellular free calcium as measured by the fluorescent dye quin-2. The calcium response is rapid and dosedependent with an ED50 of 0.12 ± 0.05 nM for leukotriene B4, 0.20 ± 0.02 nM for fMet-Leu-Phe, and 320 ± 30 nM for arachidonic acid. However, unlike fMet-Leu-Phe, leukotriene B4 at concentrations up to 70 nM does not cause a significant breakdown of any of the phosphoinositides or the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
2

Year Published

1985
1985
1989
1989

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 18 publications
4
36
2
Order By: Relevance
“…Further, several of the aforementioned cis-unsaturated fatty acids have been found to stimulate Ca2+ release from the sacroplasmic reticulum, an intracellular Ca2+ storage site, in skeletal muscle (Cheah, 1981). Consistent with our data is the observation that AA increases the [Ca2+]i in human and rabbit (Volpi et al, 1984) PMNs and degranulation by rabbit PMNs (Naccache et al, 1979 (Kajikawa et al, 1983;Nishizuka, 1984) and our data show AA to stimulate PMN PK-C at concentrations that induce degranulation. In addition, y-linolenic, linoleic and oleic acid have also been demonstrated to activate human PMN PK-C (McPhail et al, 1984) and their activating potencies correlate with their capacities to induced granule exocytosis from PMNs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Further, several of the aforementioned cis-unsaturated fatty acids have been found to stimulate Ca2+ release from the sacroplasmic reticulum, an intracellular Ca2+ storage site, in skeletal muscle (Cheah, 1981). Consistent with our data is the observation that AA increases the [Ca2+]i in human and rabbit (Volpi et al, 1984) PMNs and degranulation by rabbit PMNs (Naccache et al, 1979 (Kajikawa et al, 1983;Nishizuka, 1984) and our data show AA to stimulate PMN PK-C at concentrations that induce degranulation. In addition, y-linolenic, linoleic and oleic acid have also been demonstrated to activate human PMN PK-C (McPhail et al, 1984) and their activating potencies correlate with their capacities to induced granule exocytosis from PMNs.…”
Section: Discussionsupporting
confidence: 91%
“…The possibility that AA-induced Ca2+ mobilization was mediated by phospholipase C-catalysed hydrolysis of phosphatidylinositol 4,5-bisphosphate with the release of inositol-1,4,5-trisphosphate would appear to be negated by the report that AA has no effect on phosphatidylinositol breakdown in PMNs (Volpi et al, 1984). However, AA could facilitate Ca2+ mobilization via a direct effect on the intracellular Ca2" storage site(s).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of neutrophils with fMet-Leu-Phe has been reported to result in an increase of DAG in one study [25] but in another [26] it has been suggested that this may not occur. If this latter statement is correct, an explanation other than the one proposed here would be required for the PGEi effect on 0; generation by neutrophils stimulated with this peptide.…”
Section: Discussionmentioning
confidence: 97%
“…Chemotactic factors bind to membrane receptors on granulocytes, eliciting a wide range of responses including membrane depolarization (7), release of intracellular calcium (8), inositol phospholipid turnover (9), and protein phosphorylation (10). These signals in turn activate a full range ofgranulocyte responses including chemotaxis, degranulation, and oxygen radical production.…”
Section: Introductionmentioning
confidence: 99%